PSYCHOLOGICAL CONDITIONS OF CHARACTERS BASED ON AGE IN THE CARIYOS KIDANG TELEANGKAS MANUSCRIPT - Roslinda Azzahro; Murni Widyastuti (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
Humans as objects as well as subjects in psychological research. In a literary work, there is a character as an imaginary picture of humans in general. The psychological condition of the characters dramatically influences the storyline and point of view in the story. This study discusses the psychological condition of several characters based on age contained in the classic Javanese story in the NB 1801 manuscript entitled Cariyos Kidang Telangkas, collection of the National Library of Indonesia (PNRI). The manuscript is in the Javanese language and script, which raises the first problem: not everyone can understand Javanese script. The second problem is how age can affect the psychological condition of the characters in Cariyos Kidang Telangkas. The purpose of this research is to find out the contents of the NB 1801 manuscript, and the effect of age on the psychological condition of the characters in the story. The psychology of the characters is an important thing to study because the psychological conditions of the characters can affect the storyline through their actions and behavior of the characters. This study uses philology's methods and work steps, namely inventory to transliteration, then data and research objects use theory. Through this process, it was found that a person's age level can affect his actions, behavior, mindset, and psychological condition.